PENERAPAN TEKNOLOGI TEPAT GUNA UNTUK PENINGKATAN KUALITAS HASIL PERKEBUNAN KAKAO KELOMPOK TANI MURPUJUNG LOMBOK UTARA - Apriani, Apriani; Hadi, Sirojul; Danu Prima Arzani, Lalu; Darma Asasih, Widani (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Cocoa plantations face a number of complex and interrelated challenges. Several critical problems threatening the sustainability of cocoa farming include declining productivity due to pest infestations, inefficiencies in the management of cocoa pod husk waste, weak adoption of agronomic practices such as pruning and sanitation, and the occurrence of land degradation caused by decreasing soil organic matter content. The activities conducted included training on the production of liquid organic fertilizer from Gamal (Gliricidia sepium) leaves, instruction on proper pruning and plantation sanitation techniques, processing cocoa pod husk waste into compost, and the creation of IoT-based biopori (absorption holes). The implementation results demonstrated a significant increase in farmers' knowledge and skills, particularly in the aspects of plantation sanitation and the techniques for making organic fertilizers and pesticides from Gamal leaves. Program evaluation revealed a marked improvement in understanding: the category for 'basic knowledge' increased from 16.80 percent to 44.00 percent, and the 'comprehensive knowledge' category rose from 0.07 percent to 36.41 percent. Conversely, the 'no knowledge' category decreased from 48.40 percent to 12.33 percent. The implication of this community service project is that the empowerment program was effective in enhancing farmers' comprehension and encouraging the adoption of sustainable agricultural practices.